Hubungan Antara Pengetahuan Perawat Tentang Rekam Medis Dan Dokumentasi Keperawatan Dengan Kelengkapan Pencatatan Dokumentasi Keperawatan Di Rumah Sakit Mulia Hati Wonogiri - Swastika, Wini, Dwi Astuti, SKM., M.Kes, Sri Darnoto S.KM M.PH (2015)
Any one kind endorsement health services in the hospital is medical record which are used for completely information about medical services processes which is given.Nurses as well as medical personnels providing health services have an obligation to make the nursing documentation measures they did. The aim of this research was to determine the relationship of the nurse's knowledge about the medical record and the nursing documentation with the completeness of filling the nursing documentation. This study is an observational study with cross sectional design. The study population were all nurses and the sample of 30 nurses were involved in direct charge of medical record and 30 medical record document. Statistical tests using Chi Square with SPSS. In this research the results of bivariate analysis found a significant between the variables of knowledge about the medical record p = 0,028 and the nursing documentation p = 0,011 with the completeness of filling the nursing documentation in RS Mulia Hati Wonogiri.